OECD employment outlook 2010: moving beyond the jobs crisis (Paris, 2010)
'The OECD Employment Outlook 2010 is OECD’s annual report on employment and labour markets in the OECD area and beyond. Opening with an editorial which analyses the immediate policy challenges and provides advice for OECD governments, and a first chapter that sets out the facts and figures related to recent employment developments and sets them in the broader economic context, this volume goes on to provide analysis in three specific policy areas: the jobs impact and policy response in emerging economies, institutional and policy determinants of labour market flows, and the quality of part-time work. The volume closes with a statistical annex which provides the latest available employment data. This book includes StatLinks, URLs under each graph and table linking to spreadsheets showing the underlying data.'